Consumer knowledge and attitudes about genetically modified food products and labelling policy. (May 2015) - Vecchione, Melissa; Feldman, Charles; Wunderlich, Shahla
Abstract The purpose of this study was to examine the relationship between consumer knowledge, attitudes and behaviours towards foods containing genetically modified organisms (GMOs) and the prevalence of GMO labelling in northern New Jersey supermarkets. This cross-sectional study surveyed 331 adults, New Jersey supermarket customers (mean age 26 years old, 79.8% women). The results show a strong, positive correlation between consumer attitudes towards foods not containing GMOs and purchasing behaviour (Pearson's r = 0.701, p < 0.001) with lesser correlations between knowledge and behaviour (Pearson's r = 0.593, p < 0.001) and knowledge and attitudes (Pearson's r = 0.413, p < 0.001). GMO labelling would assist consumers in making informed purchase decisions.